2021
DOI: 10.1111/ijcs.12679
|View full text |Cite
|
Sign up to set email alerts
|

Let us be realistic: The impact of perceived brand authenticity and advertising image on consumers’ purchase intentions of food brands

Abstract: Regardless of whether you are a working or stay-at-home parent, taking care of dependent children often feels like running from breakfast to bedtime without ever catching a breath. Additionally, most parents finds themselves juggling a hectic home life while trying to nurture a career, often leaving parents feeling stressed, tired, and rushed (Pew Research Center, 2015). The "perfect storm" of dinner when children refuse to eat or finish what they were given can push parental stress levels to their peak, often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…It identifies the low online repurchase intention following perceived deception as a potential outcome of a prevention orientation. In line with regulatory focus research (Agag & El‐Masry, 2016; Filieri, 2016; Loebnitz & Grunert, 2021; Riquelme & Román, 2014), this finding establishes that prevention‐focused people are more vigilant against perceived manipulation than promotion‐focused people, they are more likely to perceive ambiguous ad claims as diagnostic of manipulative intent and, consequently, they adopt less favorable consumer behavior. In doing so, this research answers the call by Wilkins et al (2016) to explore the extent to which individuals tolerate perceived deception and the reasons for individual differences.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It identifies the low online repurchase intention following perceived deception as a potential outcome of a prevention orientation. In line with regulatory focus research (Agag & El‐Masry, 2016; Filieri, 2016; Loebnitz & Grunert, 2021; Riquelme & Román, 2014), this finding establishes that prevention‐focused people are more vigilant against perceived manipulation than promotion‐focused people, they are more likely to perceive ambiguous ad claims as diagnostic of manipulative intent and, consequently, they adopt less favorable consumer behavior. In doing so, this research answers the call by Wilkins et al (2016) to explore the extent to which individuals tolerate perceived deception and the reasons for individual differences.…”
Section: Discussionsupporting
confidence: 75%
“…Findings of this research contribute to the literature in several ways. First, although prior research has identified some factors that mitigate the negative effect of perceived deception on repurchase intention (e.g., Loebnitz & Grunert, 2021; Román, 2010), this research furthers the perceived‐deception literature by demonstrating the role of product category (hedonic vs. utilitarian) and regulatory focus in mitigating such a negative effect. To the best of our knowledge, this is the first study that explores product type and regulatory focus as the moderators that attenuate the fallouts of perceived deception.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Brand authenticity is an asset. However, the interaction of perceived brand authenticity and advertising imagery is defined by overall brand evaluation (Loebnitz & Grunert, 2022). Advertising photography and brand image are more and more inseparable and complement each other.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…However, not only the consumer's attitude towards the brand will affect the business operation, but also the emotional attachment of consumers to the brand, and even the company's digital marketing to consumers, will profoundly affect the relationship between consumer and insurance companies. In the past, domestic research on brands has mostly focused on advertising communication, including advertising story marketing, advertising image and virtual spokespersons (Loebnitz & Grunert, 2022), while online marketing is most of the discussions are focused on physical merchandises industry, and rarely explore brand and digital marketing as the research direction in the insurance industry (Garner, 2022). Online marketing research is mostly concentrated on in retail chain channels discuses on customer loyalty, service quality, and purchase intentions (Bui, 2022), therefore, this study chooses to take insurance customers as an example to explore the antecedent of brand attitudes.…”
Section: Introductionmentioning
confidence: 99%